Method for preparing vinyl chloride copolymer

The linear structure low-glass transition temperature copolymerization method is prepared by the suspension copolymerization method, which solves the problem of uneconomic molecular migration and copolymerization mixing process of plasticizer, and realizes the molecular structure and performance stability of the polyurethane-vinyl chloride copolymer.

CN119912646APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311429855.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing preparation methods for vinyl chloride copolymers, the molecular migration of plasticizers is serious, and the mixing process is not economical during the copolymerization process, which affects the stability of product performance.

Method used

The linear structure low-glass transition temperature copolymerization method is used to prepare a copolymer of vinyl polyurethane and vinyl chloride monomer of linear structures by using low-cost water-soluble organic matter as solvent, which stabilizes the chemical structure of the soft PVC resin and improves the economics of the mixing process.

Benefits of technology

The molecular structural stability and performance stability of polyurethane-vinyl chloride copolymer are achieved, the glass transition temperature is reduced, the copolymerization operation is simplified, and the production efficiency is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of vinyl chloride copolymer preparation, in particular to a method for preparing an internal plasticization type vinyl chloride copolymer by copolymerization of vinyl-terminated linear structure polyurethane and vinyl chloride monomers. The invention aims to solve the problem of plasticizer molecule migration in manufacturing of soft polyvinyl chloride products and improve a mixing process in a copolymerization process of a copolymerizable vinyl ester-terminated polymer and a vinyl chloride monomer. The invention provides a method for preparing a polymer by copolymerizing vinyl-terminated polyurethane with linear structure, low glass transition temperature and vinyl monomers such as vinyl chloride by taking a low-cost water-soluble organic matter as a solvent, so that the composition of a soft PVC resin processed product is stabilized from the chemical structure of a final product, and the stable performance of the copolymer is ensured; and the copolymerization operation is convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vinyl chloride copolymer preparation, and in particular to a method for preparing an internally plasticized vinyl chloride copolymer by copolymerizing a linear structure polyurethane containing terminal vinyl groups with a vinyl chloride monomer. Background Art

[0002] Polyvinyl chloride resin (PVC) is an important basic resin material, but the pure resin itself is brittle, has poor mechanical properties, and has low thermal stability, so it is difficult to obtain soft polyvinyl chloride processed products. In order to improve the processing performance and prepare soft PVC resin products, plasticizers with different molecular weights with ester groups as the main structural unit are usually used in the processing of polyvinyl chloride. Most of the plasticizers used as processing aids on the current market are low-molecular ester-based compounds. PVC products have molecular migration problems during use, and the performance of the products will gradually deteriorate during use. At the same time, due to the biological toxicity of low-molecular plasticizers, the use of ester-based low-molecular plasticizers is increasingly restricted. In order to improve the performance of ester-based compounds in the manufacture of polyvinyl chloride resin products, engineers and technicians use (meth) acrylate monomers with low glass transition temperatures to copolymerize with vinyl chloride monomers. Although the softening point of vinyl chloride copolymers is reduced to a certain extent, the improvement of resin performance is relatively limited. As an example of modification of macromolecular ester compounds, patent application TW93138562A proposes a method for preparing vinyl chloride copolymers by copolymerizing compounds with low glass transition temperature and containing -OC(O)C(R)=CH2 groups with vinyl chloride based monomers. Although this method can improve the migration problem of ester group compounds in plastic products, the ester group-containing compounds (terminal acryloyl poly(n-butyl acrylate)) prepared in the polymerization process are not convenient to use due to the polymer morphology. They need to be stirred and mixed with vinyl chloride monomers at a specified temperature in a polymerization kettle for at least 60 minutes, which is very unfavorable for production operations. Although other methods for preparing soft vinyl chloride copolymers use copolymerization of polyurethane and vinyl chloride, they only achieve the effect of molecular-level blending. For example, in the method for copolymerizing polyurethane and vinyl chloride with a fatty chain structure other than an ester group described in documents such as U.S. Patent No. 4,672,095, polyvinyl chloride and polyurethane do not form a stable molecular structure at the molecular level. Therefore, when the copolymer products are used for a long time, local microscopic phase separation still exists. At the same time, in the preparation of polyurethane and vinyl chloride copolymers, polyurethane and vinyl chloride monomers need to be mixed for a long time in hours to meet the requirements of uniform blending, which is not economical in terms of preparation and production process. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a vinyl chloride copolymer. In order to solve the problem of plasticizer molecular migration in the manufacture of soft polyvinyl chloride products and improve the mixing process in the copolymerization process of a copolymerizable terminal vinyl ester polymer and a vinyl chloride monomer, the present invention proposes a method for preparing a polymer by copolymerizing a linear structure, low glass transition temperature copolymerizable terminal vinyl polyurethane with a low-cost water-soluble organic substance as a solvent and vinyl monomers such as vinyl chloride. The composition of the soft PVC resin processed product is stabilized from the chemical structure of the final product, the stable performance of the copolymer is ensured, and the copolymerization operation is convenient.

[0004] The present invention is achieved through the following technical solutions: The method for preparing the vinyl chloride copolymer of the present invention comprises the following steps: (1) Preparation of linear structure low glass transition temperature copolymerizable end-vinyl polyurethane: polyether diol: diisocyanate: chain extender: vinyl end-capping agent: catalyst in a material molar ratio of 1.0-6.0: 2.0-9.0: 0.1-0.9: 0.9-0.1: 0.0001-0.01 to prepare copolymerizable end-vinyl polyurethane; (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: firstly, vinyl chloride monomer, desalted water, dispersant and oil-soluble initiator are mixed, and then a mixed solution of acrylic esters of copolymerizable vinyl-terminated polyurethane is added to carry out suspension polymerization. After the polymerization reaction is completed, a terminator is added to terminate the reaction; (3) After the copolymerization reaction is terminated, the polymer slurry obtained by the reaction is centrifugally dehydrated, dried, and sieved to obtain a soft vinyl chloride copolymer resin powder.

[0005] In step (1), the polyether diol comprises polypropylene glycol or polytetramethylene glycol having a molecular weight of 500-3000; The diisocyanate includes isophorone diisocyanate, hexamethylene diisocyanate or dicyclohexylmethane diisocyanate; in order to avoid the formation of a cross-linked structure, isocyanate compounds containing three or more isocyanate groups should not be used in the reaction, and isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate containing two isocyanate groups are preferred, because their molecular chains are stable aliphatic structures and the product molecular structure has low rigidity; The chain extender includes one or more of 1,4-butanediol and 1,6-hexanediol; the chain extender is mainly selected from alcohol-based small molecule chain extenders, and in the present invention, 1,4-butanediol and 1,6-hexanediol are preferred due to their moderate reaction activity, low cost and flexibility of polymer molecular structure; The vinyl end-capping agent is hydroxyethyl acrylate or hydroxyethyl methacrylate; The catalyst is di-n-butyltin dilaurate.

[0006] In step (1), the linear copolymerizable terminal vinyl polyurethane can be prepared by a solvent method or a bulk method. Considering the molecular weight control and the removal process of the organic solvent used later, the bulk method is preferred in the preparation of polyurethane in the present invention; The synthesis of polyurethane requires the dehydration of polyether diol, chain extender and vinyl end-capping agent to reduce the influence of moisture and ensure the purity of molecular structure. The dehydration method can be heating to above 100°C and reducing the vacuum degree, or other physical or chemical dehydration methods based on simplicity. The reaction temperature during the preparation of polyurethane is from room temperature to 120°C, preferably 60-100°C, and the reaction is preferably carried out under a nitrogen protective atmosphere; The order of adding the reaction raw materials is: firstly reacting the polyether diol with the diisocyanate to obtain a polyurethane prepolymer with a certain molecular weight, then adding a chain extender, and further adding a vinyl end-capping agent, and after sufficient reaction time, obtaining a linear copolymerizable end-group vinyl polyurethane; The prepared copolymerizable terminal vinyl polyurethane has a weight average molecular weight of 4000-200000, a glass transition temperature between -10°C and -70°C, and a linear structure of the polyurethane molecule. The molecular terminal contains a copolymerizable vinyl group. The polyurethane polymer prepared by the bulk method is a usable elastic polymer with a certain viscosity.

[0007] In step (2), the copolymer of the vinyl-terminated polyurethane containing copolymerizable olefinic bonds in the molecular chain and vinyl chloride is prepared by a free radical polymerization method, and the purity of the suspension copolymerization product is higher. The total weight of vinyl chloride monomer and copolymerizable vinyl-terminated polyurethane is 100 parts, the amount of vinyl chloride monomer is 40-95 parts, and the amount of copolymerizable vinyl-terminated polyurethane is 5-60 parts; The amount of desalted water is 120-250 parts by mass, based on 100 parts by mass of the mixture of copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer; The dispersant includes one or more of methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose, partially saponified polyvinyl alcohol, gelatin, vinyl ether-maleic anhydride copolymer and polyacrylic acid, preferably partially saponified polyvinyl alcohol, including a main dispersant and an auxiliary dispersant, the main dispersant is a polyvinyl alcohol with a medium-high alcoholysis degree of 65.0-95.0 mol%, and the auxiliary dispersant is a polyvinyl alcohol with a low alcoholysis degree of 35.0-60.0 mol%. Based on 100 parts by mass of the mixture of copolymerizable terminal vinyl polyurethane and vinyl chloride monomer, the amount of the main dispersant is 0.01-0.50 parts, preferably 0.05-0.20 parts, and the amount of the auxiliary dispersant is 0-0.50 parts, preferably 0-0.10 parts; The oil-soluble initiator includes tert-amyl peroxy pivalate, cumyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, di(2-ethylhexyl) peroxy dicarbonate or azobisisoheptonitrile of the azo type. The amount of the oil-soluble initiator is 0.01-0.20 parts, preferably 0.03-0.10 parts, based on 100 parts by mass of the mixture of the copolymerizable vinyl-terminated polyurethane and the vinyl chloride monomer; When carrying out the suspension polymerization reaction, other auxiliary agents commonly used in the suspension polymerization of vinyl chloride can be used, including chain transfer agents for molecular weight adjustment, such as mercaptoethanol, and inorganic electrolytes for stabilizing the polymerization system, such as ammonium bicarbonate, sodium hydroxide, etc., which can be used without restriction. Metal complexing agents, anti-fisheye agents, etc. can also be used. The present invention has no limitation as long as the stability of the system in the polymerization process and the final performance of the polymerization product are guaranteed.

[0008] In step (2), the polymerization temperature of the suspension copolymerization is 30-70°C, preferably 40-65°C, and stirring is continued during the reaction. Since the polymerization activity is low at a temperature below 40°C, the production efficiency is also low. When the polymerization temperature is higher than 65°C, the stability of the polymerization system will be insufficient, and the performance of the copolymer product will deteriorate, especially the yellowing of the processed product will become obvious; The final conversion rate of the copolymerizable polyurethane and vinyl chloride during the copolymerization process is 60-95%, preferably 70-90%. When the polymerization reaction pressure drop reaches the requirement, a terminator can be added to terminate the reaction. The terminator in the suspension polymerization production of PVC resin includes one or more of diethylhydroxylamine (DEHA), acetone thiosemicarbazone (ATSC), monohydric or polyhydric phenols and ester antioxidants; The terminator can remove unreacted vinyl chloride, and the resulting copolymer resin slurry is then subjected to dehydration, drying, screening and other operations to obtain the copolymer product.

[0009] Compared with the prior art, the present invention has the following beneficial effects: The polymer preparation method of the present invention can obtain a polyurethane-vinyl chloride copolymer resin with a more stable molecular structure and greatly reduce the glass transition temperature of the polymer product.

[0010] In the process of preparing linear copolymerizable terminal vinyl polyurethane polymer, the molecular weight of the final product polymer is mainly affected by factors such as the molar ratio of the three substances of polyether diol / diisocyanate / chain extender and the reaction temperature. From the perspective of molecular structure, when the molar ratio of the four substances of polyether diol: diisocyanate: chain extender: vinyl end-capping agent is 1.0-6.0: 2.0-9.0: 0.1-0.9: 0.9-0.1, a polyurethane product with a molecular weight of 8000-200000 can be obtained. Within this molecular weight range, the polyurethane molecules and the copolymerized vinyl chloride can ensure the uniformity of the molecular structure mixing, and can also avoid the excessive molecular weight affecting the fluidity of the resin processing process and the deterioration of the mechanical properties of the polymer caused by the excessive molecular weight.

[0011] When the suspension polymerization operation with vinyl chloride monomer is carried out, the mass proportion of the copolymerizable vinyl-terminated polyurethane component in the final copolymer is 20.0-70.0% based on the total mass of vinyl chloride monomer and copolymerizable vinyl-terminated polyurethane of 100 parts. If the final amount of polyurethane is less than 20.0%, the glass transition temperature of the copolymer obtained by polymerization is not significantly reduced, and the expected lower glass transition temperature of the obtained polymer cannot be given. However, if the proportion of the copolymerizable polyurethane used exceeds 70%, the glass transition temperature of the obtained copolymer is too low, and the performance of the vinyl chloride resin is not fully reflected. Not only is the glass transition temperature low, the heat resistance is poor, and the manufacturing cost will also increase significantly, so it is also disadvantageous. DETAILED DESCRIPTION

[0012] The present invention is further described below in conjunction with examples. Unless otherwise specified, all raw materials used in the examples are commercially available.

[0013] Example 1 (1) Preparation of linear structure low glass transition temperature copolymerizable vinyl-terminated polyurethane: In a 2L glass four-necked bottle equipped with a reflux condenser, a stirrer, a thermometer and a nitrogen inlet tube, 638 parts of polypropylene glycol 3000 (PPG3000, GPC arithmetic average molecular weight 3191) dehydrated under -0.098MPa vacuum and 110°C for 2 hours, 89 parts of isophorone diisocyanate (IPDI) and 0.05 parts of di-n-butyltin dilaurate (DBTDL) were added at room temperature, and then heated to 80°C under nitrogen protection and stirring. After reacting for 2 hours, 14.4 parts of 1,4-butanediol (1,4-BDO) treated with 4A molecular sieve for dehydration was added, and the reaction was continued for 2 hours. Then, 9.4 parts of hydroxyethyl acrylate (HEA) treated with 4A molecular sieve for dehydration was added, and the reaction was continued for 2 hours. The polymerization product was transferred and the temperature was lowered to obtain a linear structure containing a copolymerizable terminal vinyl polyurethane prepolymer. After analysis and testing, the GPC arithmetic average molecular weight of the obtained polymer was 25723, and the glass transition temperature Tg was -56.4°C.

[0014] (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: Into a clean 5L stainless steel pressure polymerization kettle equipped with a stirring paddle and a temperature control jacket, 1900 parts of desalted water, 0.9 parts of polyvinyl alcohol dispersant FS-20 (product of Sinopec Chongqing Chuanwei Chemical Co., Ltd., alcoholysis degree 79.5 mol%, 4 wt.% solution viscosity 48.9 mPa·s at 25°C), 0.6 parts of initiator di(2-ethylhexyl) peroxydicarbonate (EHP), and 360 parts of copolymerizable vinyl-terminated polyurethane prepared in step (1) were added. After the polymerization kettle was closed, the air in the kettle was replaced with nitrogen, and the vacuum was then drawn to below -0.090 MPa. 840 parts of vinyl chloride monomer was added, and the mixture was stirred and mixed at room temperature for 2 hours. The mixture was heated to 58°C for reaction. After 7 hours, 0.36 parts of terminator diethylhydroxylamine (DEHA) was added, and unreacted vinyl chloride monomer was discharged. The resin slurry was dehydrated to obtain a wet material, which was then fluidized and dried in a fluidized bed dryer at room temperature for 8 hours. The polyurethane-vinyl chloride copolymer resin product was obtained by sieving. Finally, 1099 g of resin dry powder was obtained, the conversion rate of vinyl chloride monomer was 88%, the copolymer polyurethane content was 32.8 wt.%, the arithmetic average particle size of the obtained resin was 239 μm, and the glass transition temperature was 18.9°C.

[0015] (3) Mechanical properties test of polyurethane-vinyl chloride copolymer The obtained copolymer was subjected to performance testing according to the polyurethane-vinyl chloride copolymer processing and testing method, and the obtained copolymer processed product had a tensile strength of 16.3 MPa at room temperature (25° C.) and a tensile strain at break of 340.2%.

[0016] Example 2 (1) Preparation of linear structure low glass transition temperature copolymerizable vinyl-terminated polyurethane: The preparation method is the same as that of Example 1, except that 900 parts of polypropylene glycol 3000, 71 parts of hexamethylene diisocyanate (HMDI), 0.09 parts of di-n-butyltin dilaurate, 9.2 parts of 1,4-butanediol, and 4.7 parts of hydroxyethyl acrylate are used. The final polymer GPC arithmetic average molecular weight is 114538, and the glass transition temperature Tg is -59.1°C.

[0017] (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: The method for preparing a vinyl chloride copolymer is the same as that in Example 1, except that 1900 parts of desalted water, 0.86 parts of polyvinyl alcohol dispersant FS-20, 0.22 parts of polyvinyl alcohol dispersant FS-10 (product of Chongqing Chuanwei Chemical Co., Ltd., Sinopec, alcoholysis degree 71.5 mol%, 4 wt.% solution viscosity at 25°C 5.5 mPa·s), 0.53 parts of initiator di(2-ethylhexyl) peroxydicarbonate (EHP), 540 parts of the copolymerizable vinyl-terminated polyurethane prepared in step (1), 660 parts of vinyl chloride monomer, 0.30 parts of terminator diethylhydroxylamine (DEHA) were added after reacting for 6.5 hours, and finally 1115 g of resin dry powder was obtained, with a vinyl chloride monomer conversion rate of 87.1 wt.%, a copolymerized polyurethane content of 48.4 wt.%, an arithmetic average particle size of the obtained resin of 256 μm, and a glass transition temperature of -4.1°C.

[0018] (3) Mechanical properties test of polyurethane-vinyl chloride copolymer The obtained copolymer was subjected to performance testing according to the polyurethane-vinyl chloride copolymer processing and testing method, and the obtained copolymer processed product had a tensile strength of 10.5 MPa at room temperature (25° C.) and a tensile strain at break of 401.9%.

[0019] Example 3 (1) Preparation of linear structure low glass transition temperature copolymerizable vinyl-terminated polyurethane: The preparation method is the same as that of Example 1, except that 900 parts of polypropylene glycol 3000, 133 parts of isophorone diisocyanate, 0.06 parts of di-n-butyltin dilaurate, 31.9 parts of 1,4-hexanediol (1,6-HDO), and 7.8 parts of hydroxyethyl methacrylate (HEMA) are used. The final polymer has a GPC arithmetic average molecular weight of 11018 and a glass transition temperature Tg of -61.8°C.

[0020] (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: The preparation method of vinyl chloride copolymer is the same as that of Example 1, except that 1900 parts of desalted water, 0.77 parts of polyvinyl alcohol dispersant FS-20, 0.19 parts of polyvinyl alcohol dispersant FS-02 (product of Chongqing Chuanwei Chemical Co., Ltd., Sinopec, alcoholysis degree 48.5 mol%, 20 wt.% solution viscosity at 25°C 9.1 mPa·s), 0.34 parts of initiator di(2-ethylhexyl) peroxydicarbonate (EHP), 720 parts of copolymerizable vinyl-terminated polyurethane prepared in step (1), 480 parts of vinyl chloride monomer, 0.25 parts of terminator diethylhydroxylamine (DEHA) were added after reacting for 6.0 hours, and finally 1130 g of resin dry powder was obtained, with a vinyl chloride monomer conversion rate of 85.5 wt.%, a copolymerized polyurethane content of 63.7 wt.%, an arithmetic average particle size of the obtained resin of 209 μm, and a glass transition temperature of -24.4°C.

[0021] (3) Mechanical properties test of polyurethane-vinyl chloride copolymer The obtained copolymer was subjected to performance testing according to the polyurethane-vinyl chloride copolymer processing and testing method, and the copolymer processed product had a tensile strength of 6.1 MPa at room temperature (25° C.) and a tensile strain at break of 690.7%.

[0022] Example 4 (1) Preparation of linear structure low glass transition temperature copolymerizable vinyl-terminated polyurethane: The preparation method is the same as that of Example 1, except that 580 parts of polytetramethylene glycol 2900 (PTMG2900, GPC arithmetic average molecular weight 3155), 89 parts of isophorone diisocyanate, 0.04 parts of di-n-butyltin dilaurate, 16.4 parts of 1,4-butanediol, and 4.7 parts of hydroxyethyl acrylate are used. The final polymer has a GPC arithmetic average molecular weight of 25434 and a glass transition temperature Tg of -66.4°C.

[0023] (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: The method for preparing the copolymer is the same as that in Example 1, except that 1900 parts of desalted water, 0.48 parts of polyvinyl alcohol dispersant FS-20, 0.24 parts of FS-10, 0.58 parts of initiator di(2-ethylhexyl) peroxydicarbonate, 480 parts of copolymerizable vinyl-terminated polyurethane prepared in step (1), 720 parts of vinyl chloride monomer, 0.40 parts of terminator diethylhydroxylamine (DEHA) are added after reacting for 7.5 hours, and finally 1124 g of resin dry powder is obtained, the vinyl chloride monomer conversion rate is 89.5 wt.%, the copolymerized polyurethane content is 42.7 wt.%, the arithmetic average particle size of the obtained resin is 297 μm, and the glass transition temperature is -1.5°C.

[0024] (3) Mechanical properties test of polyurethane-vinyl chloride copolymer The obtained copolymer was subjected to performance testing according to the polyurethane-vinyl chloride copolymer processing and testing method, and the obtained copolymer processed product had a tensile strength of 14.4 MPa at room temperature (25° C.) and a tensile strain at break of 383.2%.

[0025] The analytical method adopted in the present invention is as follows: ① Apparent density: GB / T 20022-2005.

[0026] ② Arithmetic mean particle size of resin powder: measured by Malvern Mastersizer 2000 laser particle size analyzer at room temperature.

[0027] ③ Glass transition temperature: Using the DCS method, under liquid nitrogen conditions, the temperature was lowered from room temperature to -100°C at a rate of 10°C / min, and then raised to 100°C at a rate of 10°C / min to test the glass transition temperature Tg of the sample.

[0028] ④ Tensile strength and tensile strain at break: GB / T 1040.3-2006, type 5 specimen, speed 50 mm / min.

[0029] The processing and testing methods of the polyurethane-vinyl chloride copolymer of the present invention are as follows: Take 100 parts of vinyl chloride copolymer resin powder and 2 parts of calcium zinc heat stabilizer and weigh them in proportion, add them into a high-speed mixer, stir at low speed for 4 minutes and then at high speed for 6 minutes, and then mix the mixture on a double roller at 160°C for 10 minutes. After the mixed sample is cooled, it is cut and placed in a mold, pressed into a sheet in a flat plate vulcanizer at 180°C, hot pressed for 5 minutes, deflated 3 times during the period, and cold pressed for 5 minutes. The obtained sample is cut into pieces by a universal material sample making machine, placed at room temperature for more than 24 hours, and then the performance test is carried out.

Claims

1. A method for preparing a vinyl chloride copolymer, characterized in that: The following steps are involved: (1) Preparation of linear structure low glass transition temperature copolymerizable end-vinyl polyurethane: polyether diol: diisocyanate: chain extender: vinyl end-capping agent: catalyst in a material molar ratio of 1.0-6.0: 2.0-9.0: 0.1-0.9: 0.9-0.1: 0.0001-0.01 to prepare copolymerizable end-vinyl polyurethane; (2) Suspension copolymerization of low glass transition temperature copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer: firstly, vinyl chloride monomer, desalted water, dispersant and oil-soluble initiator are mixed, and then a mixed solution of acrylic esters of copolymerizable vinyl-terminated polyurethane is added to carry out suspension polymerization. After the polymerization reaction is completed, a terminator is added to terminate the reaction; (3) After the copolymerization reaction is terminated, the polymer slurry obtained by the reaction is centrifugally dehydrated, dried, and sieved to obtain a soft vinyl chloride copolymer resin powder.

2. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The polyether diol includes polypropylene glycol or polytetramethylene glycol with a molecular weight of 500-3000.

3. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The diisocyanate includes isophorone diisocyanate, hexamethylene diisocyanate or dicyclohexylmethane diisocyanate.

4. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The weight average molecular weight of the copolymerizable terminal vinyl polyurethane prepared in step (1) is 4000-200000.

5. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The total weight of vinyl chloride monomer and copolymerizable vinyl-terminated polyurethane is 100 parts, the amount of vinyl chloride monomer used is 40-95 parts, and the amount of copolymerizable vinyl-terminated polyurethane used is 5-60 parts.

6. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: Based on 100 parts by mass of the mixture of copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer, the amount of desalted water used is 120-250 parts.

7. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The dispersant comprises a main dispersant and an auxiliary dispersant. The main dispersant is polyvinyl alcohol with a medium to high alcoholysis degree of 65.0-95.0 mol %, and the auxiliary dispersant is polyvinyl alcohol with a low alcoholysis degree of 35.0-60.0 mol %.

8. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The oil-soluble initiator includes tert-amyl peroxy pivalate, cumyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, di(2-ethylhexyl) peroxy dicarbonate or azobisisoheptonitrile of the azo type. The amount of the oil-soluble initiator is 0.01-0.20 parts based on 100 parts by mass of the mixture of copolymerizable terminal vinyl polyurethane and vinyl chloride monomer.

9. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: The polymerization temperature of the suspension copolymerization is 40-65°C.

10. The method for preparing a vinyl chloride copolymer according to claim 1, characterized in that: In the suspension copolymerization process of the copolymerizable vinyl-terminated polyurethane and vinyl chloride monomer in step (2), the final conversion rate is 60-95%.